Penyuluhan Mitigasi Bencana pada Kawasan Sempadan Pantai Galesong Utara Kabupaten Takalar - Riswal karamma; Muh Saleh Pallu; Muh Arsyad Thaha; Farauk Maricar; Rita Tahir Lopa; Mukhsan Putra Hatta; Silman P Manda; A Subhan Mustari; Bambang Bakri; Farid Maricar; A Ilda Puspita (Faculty of Engineering UNHAS, 2021)
Coastal community education is needed to maintain the balance of coastal border areas. The purpose of this activity is to increase public awareness in dealing with and reducing disaster risk and provide a basic understanding of disaster mitigation in coastal border areas. Disaster mitigation is an activity to reduce the impact of disasters. The main components that need to be considered in understanding disasters are hazard, vulnerability, resilience, and risk. An understanding of the four main components will determine how the approach and action to disaster must be taken. The data collection method was carried out by observing the coastal border area in the Takalar area, then conducting a review of data or documents related to the border area and discussions with the community who live around the coastal border in North Galesong District to complete the results of the data review. In this service activity, counseling is carried out, one of which describes the level of danger of abrasion and the efforts made to reduce the risk. The step taken as an effort to reduce the risk of abrasion is to carry out disaster mitigation efforts. Implementation of disaster mitigation counseling in coastal border areas is a form of non-structural disaster mitigation in terms of strengthening community capacity. This outreach activity motivates the community to strengthen capacity and protect the environment around the coastal border, especially to prevent abrasion.